CONCESION DE CREDITOS - Cárdenas B., Jorge (1993)
The objective of this study is to present a generic methodology to contribute to the improvement of the procedures for deciding to grant credit, and at the same time, to guide potential clients and promote a healthy and intelligible dialogue between the parties. In this way, the four famous criteria are evaluated: i) character, which refers to the customer's willingness to pay; ii) capacity, which has to do with the customer's experience in generate funds and the possibility of continuing to generate them; iii) capital, which consists of the degree of leverage; and iv) conditions, which is the collateral or guarantee offered by the subject or company requesting the credit, as well as the date of payment. Finally, the author concludes that choosing the subject of credit is a difficult task, since the financial capacity is not enough to decide the granting of credit, but takes into account the above criteria, which to the layman may seem a subtlety.